The biochemical mechanism of auxin biosynthesis by an arabidopsis YUCCA flavin-containing monooxygenase - Dai, Xinhua; Mashiguchi, Kiyoshi; Chen, Qingguo; Kasahara, Hiroyuki; Kamiya, Yuji; Ojha, Sunil; DuBois, Jennifer; Ballou, David; Zhao, Yunde (The Journal of biological chemistry, 2013)
Auxin regulates every aspect of plant growth and development. Previous genetic studies demonstrated that YUCCA (YUC) flavin-containing monooxygenases (FMOs) catalyze a rate-limiting step in auxin biosynthesis and that YUCs are essential for many developmental processes. We proposed that YUCs convert indole-3-pyruvate (IPA) to indole-3-acetate (IAA). However, the exact biochemical mechanism of YUCs has remained elusive. Here we present the biochemical characterization of recombinant Arabidopsis YUC6. Expressed in and purified from Escherichia coli, YUC6 contains FAD as a cofactor, which has peaks at 448 nm and 376 nm in the UV-visible spectrum. We show that YUC6 uses NADPH and oxygen to convert IPA to IAA. The first step of the YUC6-catalyzed reaction is the reduction of the FAD cofactor to FADH(-) by NADPH. Subsequently, FADH(-) reacts with oxygen to form a flavin-C4a-(hydro)peroxy intermediate, which we show has a maximum absorbance at 381 nm in its UV-visible spectrum. The final chemical step is the reaction of the C4a-intermediate with IPA to produce IAA. Although the sequences of the YUC enzymes are related to those of the mammalian FMOs, which oxygenate nucleophilic substrates, YUC6 oxygenates an electrophilic substrate (IPA). Nevertheless, both classes of enzymes form quasi-stable C4a-(hydro)peroxyl FAD intermediates. The YUC6 intermediate has a half-life of ∼20 s whereas that of some FMOs is >30 min. This work reveals the catalytic mechanism of the first known plant flavin monooxygenase and provides a foundation for further investigating how YUC activities are regulated in plants.